Diabetes mellitus exacerbates changes in white matter hyperintensity shapes and volume: A longitudinal study - Shihao Xu; Yan Wang; Jiahui Chen; Zhiming Pan; Wenjun Wu; Zhipeng Su; Zhen Wang (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract INTRODUCTION Although white matter hyperintensity (WMH) can progress over time, little is known about the underlying mechanisms. In addition, type 2 diabetes mellitus (T2DM) exacerbates the accumulation of WMH. Here we aimed to investigate longitudinal changes in WMH shapes and volume in older adults with and without T2DM. METHODS Participants underwent baseline and follow‐up magnetic resonance imaging (MRI). WMH volume and shape markers were automatically assessed. We compared WMH volume and shape markers at baseline and follow‐up. RESULTS A total of 200 participants were included at baseline and 181 at follow‐up. The mean age ± SD of our study participants was 69.86 ± 6.03 years; 79 (39.90%) had a history of diabetes mellitus (T2DM) and 73 (36.50%) were male. For shape markers, participants with T2DM showed more complex periventricular (eccentricity, p = 0.027) and deep WMH shape markers (fractal dimension, p = 0.002) than participants without T2DM. At baseline, there were no statistically significant differences (p > 0.05) in WMH volume when participants with T2DM were compared to participants without T2DM. At follow‐up, a more complex shape of periventricular/confluent WMH on follow‐up (concavity index, p = 0.005; inverse sphericity index, p = 0.001). In addition, total (p < 0.001), periventricular (p < 0.001), and deep (p = 0.001) WMH volumes increased significantly. DISCUSSION A more irregular shape of periventricular and deep WMH and higher WMH volumes were associated with T2DM participants. These findings suggest that WMH shape markers may be useful in determining prognosis for cerebral small vessel disease and aid in future preventive treatments. Highlights Patients with diabetes mellitus have more irregular white matter hyperintensity (WMH) shapes and increased WMH volumes. Diabetes mellitus exacerbates the changes in WMH shapes and volumes WMH shape markers might have the potential to aid in future preventive treatments and prevent clinical deterioration.